2010
DOI: 10.1007/s00436-010-1864-4
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in the prevalence and molecular epidemiology of Cryptosporidium infection in dairy cattle in the New York City Watershed

Abstract: We conducted cross-sectional studies in the New York City Watershed to ensure a valid estimate of the risk associated with Cryptosporidium infection in dairy herds. Our aims were to obtain species-specific estimates of the prevalence of Cryptosporidium in dairy cattle and to investigate seasonal variations in prevalence. We validated our empirical estimates using a Bayesian approach. Samples were collected on 32 study farms, once in each of 3 different seasons using an age-stratified sampling design. The overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
3
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 47 publications
2
10
3
1
Order By: Relevance
“…Unfortunately, we did not study the prevalence of Cryptosporidium in the autumn, so cannot comment on this season. We detected C. bovis infection in all studied seasons, in contrast to previous reports that C. bovis prevalence in pre-weaned calves peaked in autumn in China and in summer in the United States [34], [41].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Unfortunately, we did not study the prevalence of Cryptosporidium in the autumn, so cannot comment on this season. We detected C. bovis infection in all studied seasons, in contrast to previous reports that C. bovis prevalence in pre-weaned calves peaked in autumn in China and in summer in the United States [34], [41].…”
Section: Discussioncontrasting
confidence: 99%
“…in yaks peaked in the spring (28.4%), declining in the summer (22.0%), and descended to the lowest levels in the winter (17.5%). This is in accordance with the report that Cryptosporidium infection of dairy calves peaks in spring [50], but is contrary to Szonyi et al [41] and Wang et al [34] who found that summer was the dominant infection season in the United States and China, while Hamnes et al [53] found the highest prevalence in winter in Norway. The reasons for the seasonal variation in infection rates in yaks may be explained as follows: In spring in Qinghai Province, new grass has not yet grown, and yaks are fasted over the long winter.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, there appeared to be a seasonal shift in the dominant Cryptosporidium species in preweaned calves, with C. parvum peaking in summer and C. bovis peaking in autumn and winter. This finding is somewhat different from the recent observation of C. bovis dominance in summer and C. parvum dominance in spring and winter in dairy cattle in New York (38). More large studies in different areas are needed to determine whether these differences are attributable to difference in animal management.…”
contrasting
confidence: 79%